PENERAPAN METODE PEMBELAJARAN WRITING ESTAFET UNTUK MENINGKATKAN KEMAMPUAN MENULIS PANTUN SISWA KELAS IV SDN 006 RAJA BEJAMU SINABOI - Marini '; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is a Class Action Research (CAR) conducted aims to improve the ability to write rhymes fourth grade students of SDN 006 Raja Bejamu Sinaboi. Research motivated by low yields Indonesian student learning is 56.40 by the number of students as many as 20 people. This study aims to improve students' ability to write rhymes fourth grade 006 Raja bejamu Sinaboi by applying the learning model Writing Relay. This research was conducted using the instrument observation sheets, and a test sheet learning outcomes. Based on the analysis, it is known that the use of learning model can improve activity relay writing teacher from 71.42 in the first cycle of the meeting rose to 82.14 at the end of the cycle two. Furthermore activity students also increased from 67.80 in the first meeting of the cycle, increasing to 71.42 in cycle two. The ability to write poetry students also increased from 56.40 on the score increased at the end of two cycles with an average to 83.33. These research findings could prove the hypothesis of the study with the application model Writing Relay can improve relay pantun writing skills fourth grade students of SDN 006 Raja Bejamu. This means that the research hypothesis is accepted.Key Words ; Writing relay, the ability to write rhymes